Intermediate filament proteins expression and carbohydrate moieties in trophoblast and decidual cells of mature cat placenta - Fernández, Patricia Elena (2014)
The aim of this study was to characterize cytoskeletal intermediate filament proteins and glycoconjugates of syncytiotrophoblast, cytotrophoblast and decidual cells of feline endotheliochorial placenta. Samples from 12 normal pregnant female cats, after 45 ± 5 days of gestation, were obtained removing the uterine horns by hysterectomy. Sections were processed for routine observation and for immunohistochemistry using anticytokeratin, antivimentin and antidesmin antibodies. In addition, lectin histochemistry was performed using a panel of several biotinylated lectins to characterize glycosides expression profile. Cytotrophoblast and syncytiotrophoblast showed immunoreactivity only with acidic and basic cytokeratins. Decidual cells were only positive to vimentin, consistent with their origin from endometrial fibroblasts. Trophoblast expressed a broad population of glycans, highly exposing terminal N-acetyl glucosamine residues and non-sialylated galactose and N-acetyl galactosamine oligomers. Oligosaccharides bound by Phaseolus vulgaris erythroagglutinin were the only highly branched N-linked residues evidenced in cats, and they were restricted to the syncytium. Unlike results reported on humans, mice and rats on lectin affinity of decidual cells, sialid acids and complex N-linked oligosaccharides were not demonstrated in cats. Glycosylation of proteins determines many of their final properties, thus becoming essential for the embryo-maternal dialogue during implantation and placentation. Changes in glycosylation pattern have been related to pathological pregnancies in other species. Hence, the knowledge about glycosylation profile of the normal cat placenta may lead to a better understanding of both normal and pathological reproductive events.